Peran tokoh adat nagari pada pemilihan bupati - Indriani, Maiyona; Rafni, Al; Suryanef, Suryanef; Luthfi, Zaky Farid (Departemen Pendidikan Kewarganegaraan dan Ilmu Hukum Universitas Negeri Padang, 2026)
This study aims to describe the role of traditional leaders in the 2024 Pesisir Selatan Regent Election and identify supporting and inhibiting factors in the implementation of these roles in Nagari Kambang Timur. This study uses a qualitative approach. Research informants were determined through a purposive sampling technique involving niniak mamak, cadiak pintar, bundo kanduang, community leaders, and other relevant parties. The collected data were analyzed using a descriptive approach using the theories of Historical Institutionalism, Functional Institutionalism, Local Strongman, and legitimacy. Data collection techniques were carried out through in-depth interviews and documentation studies. Data validity was tested through source triangulation, diligent observation, and member checking. The results of the study indicate that traditional leaders play a real role as 1) agents of political socialization, 2) mobilizers, and 3) facilitators in the implementation of the Pilkada. These roles are realized through the delivery of political information, strengthening public participation awareness, facilitating communication between candidates and the community, as well as efforts to maintain social stability and prevent conflict during the election stages. Supporting factors for the implementation of the role of traditional leaders include 1) strong social and cultural legitimacy, 2) closeness of traditional leaders to the community, 3) high levels of community trust, 4) extensive social networks of traditional leaders, and 5) government support. Meanwhile, inhibiting factors include 1) political pragmatism, 2) lack of neutrality of traditional leaders, and 3) modernization and shifting values.